Real Estate Development through Innovative Forms of Project Financing in Selected Countries - Monika PORADOVA; Lucia SVABOVA (Communications of International Proceedings, 2020)
Project financing is an innovative financing technique that is used to raise large amounts of capital. It is currently applied to funded long-term and costly projects such as real estate. The objective of the present article is to provide an analytical overview of the issue of real estate development through innovative forms of project financing in selected countries. The present paper consists of four parts. For the first parts paper, it deals with the issue of project financing and theoretical backgrounds. The second part focuses on methods of financing investment projects through bank loans, namely investment loans, mortgage loans or supplier loans. Also describes how to obtain the results of the analysis carried out. The survey involved 15 countries where banks from leading financial companies operating in each individual country were approached and selected. The survey included 70 banks, all of which were active in the market. The third part deals with the specific results of the analysis carried out. The analysis was carried out on selected countries on the basis of geographical locations and two categories of analysis were created. The first is "Central and Eastern European Economies" and the second category is "Other European Economies". The fourth part of the article focuses on discussion and the fifth part deals with the conclusions of the addressed issue. As a result of the present paper, a comprehensive view of real estate development through innovative forms of project financing in selected countries is the result. A descriptive method, analysis, mathematical-statistical methods, graphic methods, comparison and synthesis were used in the processing of the submitted paper creation.
Keywords: Real Estate; Project Financing; Innovation; Loan Portfolios